Creating walking tracks to success: A narrative analysis of Australian Aboriginal and Torres Strait Islander nursing students' stories of success. Issue 4 (December 2016) - West, Roianne; Foster, Kim; Stewart, Lee; Usher, Kim
Abstract: Australian Aboriginal and Torres Strait Islander people have higher rates of morbidity and mortality than other Australians. One proposed strategy to improve this situation is to increase the participation of Aboriginal and Torres Strait Islander people, including Aboriginal and Torres Strait Islander nurses, in the health workforce. Although the numbers of Aboriginal and Torres Strait Islander students undertaking tertiary nursing courses have increased, completion rates have not kept pace. The study aimed to describe Aboriginal and Torres Strait Islander nursing students' experiences of enablers for successful course completion and to develop a narrative of student experience. A qualitative study using a strengths-based approach with a narrative analysis of semi-structured interview data was conducted across four schools of Nursing in Queensland, Australia. Eight final-year Aboriginal and Torres Strait Islander nursing students volunteered to participate in the study. A collective story with the overarching plotline Creating walking tracks to success was developed. Six threads of experience emerged: Making a difference, Valuing Indigeneity, Healing strength of connections, Resisting racism, Embracing support, and persevering towards completion. Key success factors included resilient attributes, building supportive connections and having positive expectations of the future, along with sustained institutional support from Aboriginal and Torres Strait Islander nurse academics and clinicians. Development of tailored resilience-building training for Aboriginal and Torres Strait Islander nursing students and appointment of Aboriginal and Torres Strait Islander academics in Schools of Nursing that include such students may facilitate future successful completions in other programs.